Analisa Perbandingan Pengaruh Penggunaan Protokol Tunneling IP Security Dengan Protokol Tunneling Layer 2 Tunneling Protocol Terhadap Quality Of Services Pada Jaringan Virtual Private Network - Sari, Linna Oktaviana; Taufano, Haza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Internet Protocol Security (IPSec) and Layer 2 Tunneling Protocol (L2TP) is a security protocol on the VPN is used to improve the security of an Internet network. Comparison of the use of these protocols may affect network performance or Quality of Services (QoS). The QoS measurement parameters measured by delay, jitter, throughput and packet loss. Network modeling scenarios using the bus topology model. Results of this study was to compare the performance of each protocol which is VPN IPSec and L2TP by measuring the QoS performance without using the protocol as a benchmark to compare their effects on QoS by using the tunneling protocol.Keywords : Virtual Private Network, IPSec, L2TP, Quality of Services